Antidote or antagonist? The role of Education Reform Advocacy Organizations in educational policymaking. Issue 3 (3rd July 2019) - Piazza, Peter
ABSTRACT: In recent years, a new breed of political organizations has had remarkable influence in American educational policymaking. Proponents of neoliberal reform, these groups have been labeled as Education Reform Advocacy Organizations, or ERAOs. I situate these organizations within the larger network of Intermediary Organizations (IOs). To understand the ways that ERAOs influence the policymaking process, I explore the role of Stand for Children, a national ERAO, in helping to pass neoliberal reform of teacher job security in Massachusetts. Using the Advocacy Coalition Framework (ACF), I explore common frames evident in debate about the organization's role in the state, and I rely on data from key stakeholder interviews, observations and policy artifacts to characterize competing arguments about the organization's political motives. I pay particularly close attention to how the organization's political identity shaped, and was shaped by, its attempts to build an advocacy coalition in the state. Throughout the case, I investigate how competing identities bumped up against each other in ways that would have a major impact on the policymaking process, and I use my analysis to generate questions about what it means for ERAOs to sustain their success over time.